Hybrid ADCs, Smart Sensors for the IoT, and Sub-1V & Advanced Node Analog Circuit Design Advances in Analog Circuit Design 2017 - Harpe, Pieter; Makinwa, Kofi A. A.; Baschirotto, Andrea; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book is based on the 18 tutorials presented during the 26th workshop on Advances in Analog Circuit Design. Expert designers present readers with information about a variety of topics at the frontier of analog circuit design, with specific contributions focusing on hybrid ADCs, smart sensors for the IoT, sub-1V and advanced-node analog circuit design. This book serves as a valuable reference to the state-of-the-art, for anyone involved in analog circuit research and development.  .
Part I.Hybrid Data Converters -- Chapter 1. HYBRID DATA CONVERTERS -- Hybrid and segmented ADC techniques to optimize power efficiency and area. The case of a 0.076mm2 600MS/s 12b SAR- ADC -- Chapter 3. Interleaved Pipelined Sar Adcs: Combined Power for Efficient Accurate High-Speed Conversion -- Chapter 4.Hybrid Vco Based 0-1 Mash and Hybrid Sar._ Chapter 5. A Hybrid Architecture for a Reconfigurable Sar Adc._chapter 6. A Hybrid ADC for High Resolution: The Zoom ADC -- Part II.Smart Sensors for the IoT -- Chapter 7.Advances in Biomedical Sensor Systems for Wearable Health -- Chapter 8.An Ultra-Lowpower, Robust Photoplethysmographic Readout Exploiting Compressive Sampling, Artifact Reduction and Sensor Fusion -- Chapter 9.A 32kHz-DTCXO RTC Module with an Overall Accuracy of ±1ppm and an All-Digital 0.1ppm Compensation Resolution Scheme -- Chapter 10.Energy-Efficient High-Resolution Resistor-Based Temperature Sensors -- Chapter 11. A High-Resolution Self-Oscillating Integrating Dual-Slope CDC For Mems Sensors -- Chapter 12. Ultra-Low Power Charge-Pump Based Bandgap References -- Part III.Sub-1V & Advanced-Node Analog Circuit Design.-Chapter 13. FD-SOI Technology, Advantages for Analog/RF and Mixed-Signal Designs -- Chapter 14.Analog/Mixed-signal Design In Finfet Technologies -- Chapter 15.Analog circuits in 28nm and 14nm FinFET -- Chapter 16.Pipeline and SAR ADCS for Advanced Nodes -- Chapter 17.Time-Based Biomedical Readout in Ultra-Low Voltage, Small-Scale CMOS Technology -- Chapter 18.A 4.4mW-TX, 3.6mW-RX Fully Integrated Bluetooth Low-Energy Transceiver for IoT Applications.
Keywords: Electronic circuits; Microprocessors; Computer architecture; Electronic Circuits and Systems; Processor Architectures